Three-dimensional choroidal vascularity index and choroidal thickness in fellow eyes of acute and chronic primary angle-closure using swept-source optical coherence tomography - Hai-Li Huang; Guan-Hong Wang; Liang-Liang Niu; Xing-Huai Sun (International Journal of Ophthalmology, 2024)
AIM: To compare the three-dimensional choroidal vascularity index (CVI) and choroidal thickness between fellow eyes of acute primary angle-closure (F-APAC) and chronic primary angle-closure glaucoma (F-CPACG) and the eyes of normal controls. METHODS: This study included 37 patients with unilateral APAC, 37 with asymmetric CPACG without prior treatment, and 36 healthy participants. Using swept-source optical coherence tomography (SS-OCT), the macular and peripapillary choroidal thickness and three-dimensional CVI were measured and compared globally and sectorally. Pearson's correlation analysis and multivariate regression models were used to evaluate choroidal thickness or CVI with related factors. RESULTS: The mean subfoveal CVIs were 0.35±0.10, 0.33±0.09, and 0.29±0.04, and the mean subfoveal choroidal thickness were 315.62±52.92, 306.22±59.29, and 262.69±45.55 μm in the F-APAC, F-CPACG, and normal groups, respectively. All macular sectors showed significantly higher CVIs and choroidal thickness in the F-APAC and F-CPACG eyes than in the normal eyes (P<0.05), while there were no significant differences between the F-APAC and F-CPACG eyes. In the peripapillary region, the mean overall CVIs were 0.21±0.08, 0.20±0.08, and 0.19±0.05, and the mean overall choroidal thickness were 180.45±54.18, 174.82±50.67, and 176.18±37.94 μm in the F-APAC, F-CPACG, and normal groups, respectively. There were no significant differences between any of the two groups in all peripapillary sectors. Younger age, shorter axial length, and the F-APAC or F-CPACG diagnosis were significantly associated with higher subfoveal CVI and thicker subfoveal choroidal thickness (P<0.05). CONCLUSION: The fellow eyes of unilateral APAC or asymmetric CPACG have higher macular CVI and choroidal thickness than those of the normal controls. Neither CVI nor choroidal thickness can distinguish between eyes predisposed to APAC or CPACG. A thicker choroid with a higher vascular volume may play a role in the pathogenesis of primary angle-closure glaucoma.